Implementasi Pendidikan Panca Waluya dalam Keluarga Sebagai Upaya Mewujudkan Generasi Emas pada Tahun 2045 - Yusuf, Yusfita; Asmara, Andes Safrandes; Nugraha, Novan Bayu; Riswandiah, Ekky (Universitas Perjuangan Tasikmalaya, 2026)
Character education based on local noble values is key in forming a superior generation. Panca Waluya is a character education concept based on Sundanese local wisdom that includes five main values: Cageur (healthy), Bageur (good), Bener (correct), Pinter (intelligent), and Singer (skilled). This concept can be applied in families as a foundation for children's character formation. The background of this community service focuses on the importance of implementing Panca Waluya education in families to create a quality generation, capable of facing global challenges in the future, especially in realizing the Golden Generation of 2045. The methods used in this community service include counseling, training, and group discussions with parents on how to instill Panca Waluya values in everyday life. The results of this community service show that the parents involved are beginning to understand and apply the principles of Panca Waluya in their parenting patterns and improved quality relationships within the family and character. Strengthening Panca Waluya education in the family environment is believed to be a strategic step towards realizing Indonesia's Golden Generation in 2045.